Standar Proses di SMA Negeri 1 Klari : Implementasi Kurikulum Merdeka Untuk Meningkatkan Kualitas Pembelajaran - Nazwa Nur Aulia Syam; Fathin Ihsanul Haq; Sekar Wulan Suci; Muhammad Aly Fadillah; Hinggil Permana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study discusses the implementation of learning process standards as a key element in improving the quality of education, especially within the framework of the Independent Curriculum. The problem found in the field shows that the application of process standards has not been optimal, as many teachers still focus only on cognitive aspects without balancing affective and psychomotor elements. This research aims to analyze the implementation of process standards in learning at SMA Negeri 1 Klari, which has implemented the Independent Curriculum through the School Driving Program. The study used a qualitative approach with a case study design, involving principals, teachers, and students as participants. Data were collected through observation, in-depth interviews, and documentation, and analyzed using Miles and Huberman’s interactive model, including data reduction, presentation, and conclusion drawing. The results indicate that the consistent implementation of process standards—covering planning, implementation, assessment, and supervision—has significantly improved the quality of learning. The findings also show that the process standards serve not only as a technical guideline but also as a pedagogical framework that encourages teacher professionalism, active learning, and the development of students’ character in line with the Profile of Pancasila Students. In the context of the Independent Curriculum, process standards remain relevant in realizing flexible, contextual, and student-centered learning through project-based and collaborative approaches.